Drawings in the world. On multiscalarity and scales outside the representation - Giovanni Durbiano; Tommaso Listo (Agathón)
The article relates the concept of architectural scale with the philosophical and political implications of the world representation action implicit in every scalar operation. Drawing from a certain philosophical tradition about representation, it follows that the scalar attribution can be interpreted as an attempt to perform a form of control over the represented through the drawing, with the purpose to legitimize the author and the scientificity of the architectural discipline in theories and Schools. However, this paradigm, which made the Italian post-war architecture so successful, is put in crisis by the nature of the problems requiring design and projection. From these considerations, a conceptualization of multiscalarity is proposed, focusing on the project's agency in the world, rather than from an introjection of the latter into the designer intentions.